2021
DOI: 10.21608/efmj.2021.25628.1016
|View full text |Cite
|
Sign up to set email alerts
|

Workplace Violence against Female Nurses in Menoufia Governorate, Egypt: an Epidemiological Study

Abstract: Background: Workplace violence (WPV) against nurses becomes a global problem with negative sequel on healthcare providers. Objectives: to evaluate the prevalence of WPV against Egyptian female nurses and to determine its sociodemographic and occupational risk factors. Methods: This crosssectional study was performed at different level hospitals in Menoufia governorate, Egypt. A total of 1023 nurses were included, with response rate (94.82%): Nine hundred and seventy nurses. They worked on primary (n=120), seco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 8 publications
(8 reference statements)
2
4
0
Order By: Relevance
“…Most of the violent events were committed by visitors/patients' relatives (68.4%) (Table 1) and this agreed with the finding of other studies (Abdel-Salam, 2014; Abou-ElWafa et al, 2015; Abdellah and Salama, 2017; Gabr et al, 2021;Ghareeb et al, 2021). This can be attributed to the strong family and social bonds which characterize the Egyptian population.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Most of the violent events were committed by visitors/patients' relatives (68.4%) (Table 1) and this agreed with the finding of other studies (Abdel-Salam, 2014; Abou-ElWafa et al, 2015; Abdellah and Salama, 2017; Gabr et al, 2021;Ghareeb et al, 2021). This can be attributed to the strong family and social bonds which characterize the Egyptian population.…”
Section: Discussionsupporting
confidence: 90%
“…In Egypt, many studies were conducted to identify the incidence, pattern, and predictors of workplace violence against HCWs ( Gabr et al, 2021). Due to its great effects on the HCWs and the healthcare system as a whole, this phenomenon needs to be continuously monitored to identify its trend and if there are any additional risk factors involved in violence occurrence.…”
Section: Workplacementioning
confidence: 99%
“…The participants of the present study reported a greater frequency of violence during night shifts. Similar findings were reported by Gabr et al [ 17 ] who found nurses in Menoufia governorate hospitals were exposed to a higher frequency of WPV during night shifts compared to day shifts. These findings also corroborate a previous study by D’Ettorre et al .…”
Section: Discussionsupporting
confidence: 90%
“…The present study found sexual violence was the next most common form of violence at the EDs of ASUH (48.1%). The prevalence of sexual violence in the EDs of other governorates has previously been reported as 30.9% at the Emergency Hospital of Mansoura University [ 15 ]; 58.1% at Sohag University Hospital [ 16 ]; and 14.12% in Menoufia governorate hospitals [ 17 ]. The prevalence of sexual violence to nurses was reported as 70.2% at Tanta University Hospital [ 18 ].…”
Section: Discussionmentioning
confidence: 99%
“…The participants were recruited across 162 (numbers ranging from 1 to 23) health facilities. The studies were conducted in 10 different countries, with majority conducted in Ethiopia ( n = 8), 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 followed by Egypt ( n = 7), 28 , 29 , 30 , 31 , 32 , 33 , 34 South Africa ( n = 3), 35 , 36 , 37 Ghana ( n = 2), 38 , 39 Nigeria ( n = 2), 40 , 41 and 1 each from Gambia, 42 Malawi, 43 Kenya, 44 Rwanda, 45 and Tanzania. 46 The quality of the studies ranged from 3 to 9, with majority ( n = 16) having low risk of bias (Table S2 ).…”
Section: Resultsmentioning
confidence: 99%